CASE STUDY OF PLEOMORPHIC RHABDOMYOSARCOMA IN PATIENT WITH NEUROFIBROMATOSIS TYPE-1 - Khan, Abu baker; Ahmed, Aftab; Muhammad, Ilyas (Journal of Ayub Medical College Abbottabad, 2021)
Background A 42-year-old man, known case of neurofibromatosis type 1 with cafÃ© au late spots on trunk and extremities, neurofibromas, axillary freckling, pseudoarthrosis of distal tibia. He presented to the district cancer hospital with complaint of huge mass on lateral chest wall. Incisional biopsy was done and case was diagnosed with pleomorphic rhabdomyosarcoma. Immune/histochemical staining is positive for desmin. Rhabdomyosarcoma is a malignant soft tissue tumour with rare incidence in general population. There are few cases of pleomorphic rhabdomyosarcoma in NF 1 patient are reported in literature. This case study reports a rare occurrence of rhabdomyosarcoma in adult neurofibromatosis 1 patient.